Analisis Kebutuhan Pengembangan Flashcard untuk Game Based Learning pada Materi Jamur - Nailul Hasanah; Heffi Alberida (Al-Alam: Islamic Science Education Journal, 2026)
Biology learning needs to be conducted consciously, meaningfully, and joyfully by considering the characteristics of the material and the needs of students. This study aims to analyze the need for flashcard media development for game-based learning on fungi material for Phase E high school students. The study used a descriptive method with quantitative and qualitative approaches. The study was conducted at SMAN 17 Padang for Phase E students. Data were collected using teacher and student needs questionnaires, then analyzed descriptively through percentages and grouping of open-ended answers. The results of the analysis show that Biology learning is still dominated by lectures and questions and answers with the use of media in the form of Student Activity Sheets and crosswords. The media used do not fully facilitate the activities of observing images, grouping concepts, recalling information discussing answers, and obtaining feedback. Therefore, flashcards are needed that present fungi material visually and concisely and are used in games that have goals, rules, challenges, turns, and feedback. The game is designed through the stages of memorize, recall, and examine. The results of the analysis indicate that the development of flashcards for game-based learning is needed to support more active, meaningful, and joyful Biology learning.